GAMBARAN PENGETAHUAN DAN PERAN ORANG TUA TENTANG PERILAKU KONSUMSI JAJANAN PADA ANAK USIA SEKOLAH DASAR DI SD GMIT MANUMUTI TAHUN 2020 - Handriana Gustin Jelahut; Aysanti Yuliana Paulus; Maria Paula Marla Nahak (CHMK HEALTH JOURNAL, 2021)
Food poisoning is still a public health problem for which services must be prioritized. The factors causing the behavior of consuming snacks for school age children are knowledge factors, the role of parents / family. Parents who have a good knowledge of snack foods will be able to apply their abilities to their children in choosing the snack foods they consume, so that they can meet their nutritional needs. This study aims to describe the knowledge and role of parents regarding the behavior of consumption of snacks in elementary school age children at SD GMIT Manumuti. The research method used quantitative with a descriptive approach, conducted at SD GMIT Manumuti with a target population of 438 respondents. Sampling using cluster random sampling & proportional stratified random sampling of 80 respondents. Data were collected using a questionnaire sheet. The results of the research describe the knowledge and role of parents regarding snack consumption behavior in elementary school age children at SD GMIT Manumuti obtained from 80 respondents showing a good picture of parental knowledge 47 respondents (58.8%), quite 26 respondents (32.5%) and less well 7 respondents (8.8%), while for the role of good parents, 48 ​​respondents (60.0%), only 26 respondents (32.5%), and less good 6 respondents (7.5%). From the research results, it is hoped that parents who are knowledgeable and have a good role must retain existing knowledge in order to help or provide good support for children who consume. Keywords: Knowledge, The Role Of Parents, Snack Consumption Behavior.